THE STATUS OF RHEUMATOLOGY CARE TO ADOLESCENTS WITH LOCOMOTOR APPARATUS PATHOLOGY IN THE ORENBURG REGION - G G Bagirova (Научно-практическая ревматология)
The paper gives the results of clinical and epidemiological studies conducted among adolescents in different years. It shows their more complaints about the state of the locomotor apparatus than their more polyclinic visits and presents data on the diagnosis of a specific rheumatic disease. Transfer of adolescents to be served at children's polyclinics has not improved the detection rates for locomotor system diseases. Attention is drawn to the fact that it is necessary to set up an independent rheumatology service at the children's polyclinics and it is expedient to return the adolescent service to the general practice network.